en - Evellyn Wardhana; I Made Suastra; Ni Luh Nyoman Seri Malini (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2023)
This study aims to identify the women’s language features in Crazy Rich Asians movie. The women’s language features are identified using the theory of language and woman’s place proposed by Lakoff (2004). This is a qualitative study that used documentation and observation checklist method in collecting the data. In analyzing the data, this study applied the content analysis method. The result of the analysis was presented descriptively using the informal method. The analysis comes to the conclusion that the Crazy Rich Asian movie contains all women’s language features. There are ten women’s language features, namely lexical hedges, tag questions, rising intonation, empty adjectives, precise color terms, intensifiers, hypercorrect grammar, superpolite forms, avoidance of swearwords, and emphatic stress.